Influencia de la innovación en la competitividad de las medianas empresas del Ecuador - Jaramillo Paredes, Marcia Fabiola; Romero Hidalgo, Oscar Mauricio; Aguirre Benalcázar, Martha Cecilia; Ruiz Carrillo, Jonathan Alexander (Cuestiones Políticas, 2020)
This study had as an analysis of the influence of innovation on the competitiveness of medium-sized enterprises in Ecuador. The authors to innovation as the action of generating ideas through the management of knowledge of the use of technology, in order to influence the competitiveness of companies through the generation of added value in the offer of products and services. The methodology of the present article was developed as a non-experimental design of a transversal, exploratory and fundamentally bibliographic type to reference different texts and business contexts. In essence, it was a review work close to hermeneutics. The most reserve conclusions include that innovation as a comprehensive process that, seeking to make the most of the productive capacities of a given company, has implications and competitiveness, on the one hand, increases the quantity and quality of the services and goods that occur at the same time reducing costs; on the other hand, it affects the range that SMEs give their customers for their needs and desires with quality offers in a context of increasing national and global competence.